Epilepsy: The Next Generation Drugs (A Review) (Global Journal of Medical Research, 2014)
Seizures are common and are treated in all branches of medicine. Approximately 10% of the population will have one or more seizures during their lifetime. Seizures are symptoms that occur in acute illness, ie, provoked seizures, or in epilepsy, ie, unprovoked seizures. Antiepileptic drugs (AEDs) are pharmacologic agents used to reduce the frequency of epileptic seizures. "Antiepileptic" drug is a misnomer, because these drugs are effective as symptomatic treatment of seizures, i.e., the symptoms of epilepsy, not as treatment of epilepsy itself. Recent discoveries in molecular biology and genetics have elucidated a genetic basis for some epilepsy syndromes, which will lead to new treatments. This review include new AEDs viz; Ganaxolone, Eslicarbazepine acetate, Fluorofel-bamate, Huperzine A, Carisbamate (RWJ-333369), Brivaracetam (ucb 34714), 2-Deoxy-D-glucose, Retigabine, T2000 , T2007, Valrocemide, Tonabersat (SB-220453), YKP3089, Propyl isopropyl acetamide, JZP-4, ICA-105665, NAX-5055, Perampanel and Valpromide.